2020
DOI: 10.1128/mbio.02691-19
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Coral Microbiome: the Influence of Temperature and Microbial Network

Abstract: Host-associated microbial communities are shaped by extrinsic and intrinsic factors to the holobiont organism. Environmental factors and microbe-microbe interactions act simultaneously on the microbial community structure, making the microbiome dynamics challenging to predict. The coral microbiome is essential to the health of coral reefs and sensitive to environmental changes. Here, we develop a dynamic model to determine the microbial community structure associated with the surface mucus layer (SML) of coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 110 publications
(67 reference statements)
0
73
0
Order By: Relevance
“…The overall lower correlation may be attributable to site-speci c bacterial community composition differences. Corals from the GoA, however, exhibited a low correlation between replicate colonies at 30° and 33 °C that increased considerably at 36 °C, due to the substantial relative increase of Vibrionaceae and Rhodobacteraceae, driving the similarity between samples and indicating dysbiosis/loss of microbiome structure, as alluded earlier (Sweet and Bulling 2017;Boilard et al 2020;Lima et al 2020). Thus, the decreasing correlation coe cient(s) with increasing temperature observed in GoA corals is that of a population approaching a tipping point with subsequent systemic collapse: GoA corals ramp up their response to the increasing stressor until they reach a tipping point upon which the system collapses.…”
Section: Signatures Of Thermal Tolerance Across Regions and Coral Holmentioning
confidence: 78%
“…The overall lower correlation may be attributable to site-speci c bacterial community composition differences. Corals from the GoA, however, exhibited a low correlation between replicate colonies at 30° and 33 °C that increased considerably at 36 °C, due to the substantial relative increase of Vibrionaceae and Rhodobacteraceae, driving the similarity between samples and indicating dysbiosis/loss of microbiome structure, as alluded earlier (Sweet and Bulling 2017;Boilard et al 2020;Lima et al 2020). Thus, the decreasing correlation coe cient(s) with increasing temperature observed in GoA corals is that of a population approaching a tipping point with subsequent systemic collapse: GoA corals ramp up their response to the increasing stressor until they reach a tipping point upon which the system collapses.…”
Section: Signatures Of Thermal Tolerance Across Regions and Coral Holmentioning
confidence: 78%
“…Heat-stressed corals preferentially fed on Synechococcus to access the high nitrogen content in their cells and to compensate for the loss of nitrogen from algal endosymbiont Symbiodiniaceae during recovery from bleaching (71). The inner lagoon patch reefs in Bermuda are exposed to greater environmental fluctuations, particularly changes in temperature (45)(46)(47)51). Therefore, the high abundance of Synechococcus in the water column and in the SML of P. strigosa could be contributing to the energy transfer from pelagic to benthic trophic levels, and to the coral thermal tolerance in the inner lagoon reefs of Bermuda.…”
Section: The Coral Sml Microbiome From a Fluctuating Environment Provides More Services Related To Nutrient Cycling Stress Tolerance And mentioning
confidence: 99%
“…We selected P. strigosa as the coral host species because it is widely distributed across the Bermuda platform. The reef zones sampled were approximately 8 km apart (51) and P. strigosa is a broadcast spawner; therefore, there is a high likelihood that gene flow between the coral hosts colonizing inner and outer reefs is maintained and that the host genetics is not structured into different populations. Indeed, studies on other species have indicated high genetic exchange among reef sites in Bermuda (52,53).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations